The impact of fall risk assessment on nurse fears, patient falls, and functional ability in long-term care. Issue 11 (21st May 2016) - Dever Fitzgerald, Theresa; Hadjistavropoulos, Thomas; Williams, Jaime; Lix, Lisa; Zahir, Sharmeen; Alfano, Dennis; Scudds, Rhonda
Abstract: Purpose : The purpose of this study was to determine whether providing fall risk information to long-term care (LTC) nurses affects restraint use, activities of daily living (ADL), falls, and nurse fears about patient falls. Methods : One-hundred and fifty LTC residents were randomized to a fall risk assessment intervention or care-as-usual group. Hypotheses were tested using analyses of variance and path analyses. Results : Restraint use was associated with lower ADL scores. In the intervention group, there ceased to be significant relationships between nurse fears about falls and patient falls (after controlling for actual patient risk; post-intervention, nurse fears about falls were based on realistic appraisals), and between fears and restraints (i.e. unjustified nurse fears became less likely to lead to unjustified restraint use). No group differences in falls were identified. Conclusion : Despite a lack of group differences in falls, results show initial promise in potentially impacting resident care. Increasing intervention intensity may lead to fall reductions in future research. Implications for Rehabilitation: Given the high prevalence rates of falls in LTC and associated injuries, prevention programs are important. Nurse fears about patient falls may impact upon restraint use which, when excessive, can interfere with the patient's ability to perform ADL. Excessive restraint use, due to unjustified nurse fears, could also lead to falls. Providing accurate, concise information to nursing staff about patient fall risk may aid in reducing the association between unjustified nurse fears and the resulting restraint use that can have potential negative consequences.